The Interpersonal Collaboration in Stroke Emergency Management in Primary Care: An Evaluation of Medical Team Effectiveness: Interpersonal Collaboration in Stroke Emergency Management in Primary Care: An Evaluation of Medical Team Effectiveness - evianta, Mars (JURNAL KESMAS DAN GIZI (JKG), 2024)
Collaboration in stroke management requires an interdisciplinary approach to provide optimal care for patients. Given the complexity of stroke and its health risks, the involvement of various healthcare professions is crucial to ensuring comprehensive management. To address this, innovative care models such as interprofessional collaboration (IPC) involving pharmacists, nurses, and doctors in primary care have been proposed. This collaboration aims to improve patient care outcomes, reduce healthcare costs, and enhance the effectiveness of the healthcare team. However, the implementation of this collaboration still faces challenges, such as a lack of effective communication and unclear roles between professions. Therefore, it is essential to strengthen communication and role definition within the interprofessional team to improve the effectiveness of interpersonal collaboration in stroke emergency management in primary care settings. The World Health Organization (WHO) states that interprofessional collaboration involves various healthcare workers from different professional backgrounds working together with patients.